An electron microscopic study of early gonadogenesis in the hermaphroditic appendicularian Oikopleura gracilis (Tunicata, Oikopleuridae). Issue 2 (3rd April 2019) - Savelieva, Anna V.
ABSTRACT: The postembryonic development of the gonad in the hermaphroditic appendicularian O. gracilis was studied using transmission electron microscopy. The primordial germ cells were detected first in 10-h-old larvae and represent migrating primordial germ syncytium (mPGS) localized in the hemocoel of the tail/trunk junction and several haemocoel areas of the digestive compartment. The mPGS consisted of primordial germ nuclei (PGN) 2 μm in diameter, and elongate somatic-line nuclei 1.8 μm in diameter. In 12.5-h-old juveniles the gonad primordium 40 × 90 μm in size, was separated by a narrow space of haemocoel between the gut and the epidermis of the reproductive compartment. The gonad primordium consisted of the central syncytial part of primordial germ nuclei (PGN), enclosing a single layer of somatic epithelium. In 3-day-old juveniles, the gonad was differentiated into testis and ovary. The testis, 400 × 550 μm in size, is a syncytium of spermatogonial nuclei, covered by a single layer of somatic epithelium. The ovaries, 350 × 850 μm in size, consist of a syncytium with nurse nuclei and meiotic nuclei. The hermaphroditic gonad originates from extragonadal mPGS. Early gonadogenesis in appendicularians has ultrastructural features in common with early gonadogenesis in ascidians.